KEWENANGAN KEPALA DAERAH DALAM PENETAPAN IZIN PEMANFAATAN RUANG DI KABUPATEN BADUNG - Pradnyani, I Gusti Ayu; Sirtha, I Nyoman (Kertha Negara : Journal Ilmu Hukum, 2013)
This paper has the title "Head of the Authority in the determination of land use permits in Badung regency". Regional Head has the authority to grant the motion control functionality to the growing development of the construction so as not to deviate from what is prescribed by the Government. The research method used is a normative legal research methods, research done by the rule of law and legislation. In this paper the issues raised is how the head of the local authority in setting the permit utilization of space in Badung regency and how the presence of associated permits the use of space in the arrangement of space in Badung regency. Conclusion authority in setting the regional head permits the utilization of space in Badung regency is the Regional Head and issued the permit in the presence of space utilization in Badung regency is the direction in controlling the spatial arrangement.
Keywords: establishment permit, space utilization, Regulatory - Invitation